Improving the Theoretical and Methodological Framework for Implementing Digital Twin Technology in Various Sectors of Agriculture - Alexander Semin; Denis Mironov; Mikhail Kislitskiy; Alexander Zasypkin; Valery Ivanov (Emerging Science Journal, 2023)
The aim of this study is to systematize and improve the theoretical and methodological framework for implementing digital twin technology. The study focuses on digital twins in agriculture. This paper is designed to solve the scientific problem associated with the development of a methodological framework for the implementation of digital twins in the work of agricultural organizations. Using methods of analysis of socio-economic phenomena and processes on the basis of a set of scientific approaches, economic-statistical analysis, and others, the study considers the importance of digital twins of agricultural machinery and equipment, identifies trends in agriculture determined by digitalization, and suggests promising areas for digital twins of agricultural machinery and equipment. This paper also examines the theoretical basis for the implementation of digital twin technology in the agricultural sector of production. New research results complement the theoretical provisions on the essence of digital twin technology; develop the methodological provisions of digital twin technology, represented by the study of their significance, principles, and features of operation. The study may be seen as academically novel as it reveals the prerequisites for implementing digital technology in agriculture as well as clarifies and improves the theoretical and methodological provisions of the application of digital twin technology in various sectors of agriculture. Doi: 10.28991/ESJ-2023-07-04-05 Full Text: PDF